The cold tongue in the South China Sea during boreal winter and its interaction with the atmosphere - Varikoden, H.; Samah, A.A.; Babu, C.A. (Science Press, 2010)
A distinct cold tongue has recently been noticed in the South China Sea during the winter monsoon, with the cold tongue temperature minimum occurring in the January or February. This cold tongue shows significant links with the Maritime Continent's rainfall during the winter period. The cold tongue and its interaction with the Maritime Continent's weather were studied using Reynolds SST data, wind fields from the NCEP-NCAR reanalysis dataset and the quikSCAT dataset. In addition, rainfall from the GOES Precipitation Index (GPI) for the periods 2000 to 2008 was also used. The propagation of the cold tongue towards the south is explained using wind dynamics and the western boundary current. During the period of strong cold tongue, the surface wind is strong and the western boundary current advects the cold tongue to the south. During the period of strong winds the zonal gradient of SST is high [0.5A degrees C (25 km)(-1)]. The cold tongue plays an important role in regulating the climate over the Maritime Continent. It creates a zonal/meridional SST gradient and this gradient ultimately leads in the formation of convection. Hence, two maximum precipitation zones are found in the Maritime Continent, with a zone of relatively lower precipitation between, which coincides with the cold tongue's regions. It was found that the precipitation zones have strong links with the intensity of the cold tongue. During stronger cold tongue periods the precipitation on either side of the cold tongue is considerably greater than during weaker cold tongue periods. The features of convection on the eastern and western sides of the cold tongue behave differently. On the eastern side convection is preceded by one day with SST gradient, while on the western side it is four days.